Sikap Toleransi Beragama Peserta Didik Kelas X di SMA YPI Tunas Bangsa Palembang - Dian Safitri; Nurul Haeniah; Sri Maryati; Afif Alfiyanto; Muhammad Ghazali (LP2M IAIN Sultan Amai Gorontalo, 2022)
The purpose of this study was to describe the attitude of religious tolerance of class X students at YPI Tunas Bangsa Palembang Senior High School. How religious tolerance is carried out by class X students from various religions and how student tolerance is formed among them. The method used in this research is descriptive research method. This research was conducted at YPI Tunas Bangsa Palembang Senior High School in class X. The sample collection technique used the purposive sampling method with the criteria of all students in class X YPI Tunas Bangsa Senior High School, namely 5 non-Muslim students and 5 Muslim students. Data were collected through interviews and direct observation. The results of this study indicate that: 1) the attitudes of students at YPI Tunas Bangsa Senior High School are very flexible in the relationship between Muslim students and non-Muslim students; 2) the treatment of students with different religions is the same without any difference, both in terms of mental and learning needs; 3) students respect each other, respect differences, recognize and allow the rights that exist in each religion; 4) students show enthusiasm in building friendships; 5) religious differences do not become a dividing wall between them; 6) Student solidarity is built on tolerance in everyday life at school.